Application of STEAM Methodologies in the Rural Sector: Its Impact as Innovative Teaching - Núñez Zavala, Christian Xavier; Isín Vilema, Manuel David; Silva Castillo, Jorge Noé; Peñafiel Barros, Geonatan Octavio; Pailiacho Yucta, Hernán Ramiro; Morales, Ruth Tatiana Fonseca (Journal of Posthumanism, 2025)
This study analyzes the effectiveness of STEAM methodology in rural education at the Simón Rodríguez Rural Educational Unit located in Riobamba, Ecuador. A quasi-experimental design with pre- and post-tests was applied to 129 students from 11 to 15 years old, applying a model structured in six phases of STEAM methodology: (1) Introduction Step, where STEAM was taught with hands-on experiments and motivational activities; (2) Creation Step, which involved the design of specific content that allows meeting the expected competencies; (3) Exploration Step, where it was possible to introduce students to technological tools, educational robotics and problem solving through project-based learning; (4) Practical Step, where the acquired knowledge was tested to solve real-life challenges; (5) Elaboration Step, where STEAM-related projects were presented by students to the school and their families to gain community support in order to foster self-efficacy and critical thinking skills; and (6) Reflection Step, where students were encouraged to transfer their learning to other contexts, thus enhancing school, family, and community integration. The results showed a significant improvement in problem solving, which increased by 31.25%, in confidence with the use of self-solving technology, which improved by 13.49%, and in cognitive skills where there was an improvement in computational thinking of 28.73%. In addition, the increase in family participation was 65%, reflecting a stronger connection between the school and the community. Based on the discussions of the results, it can be inferred that the application of the STEAM approach in rural settings improves science and technology learning, while also developing self-esteem, creativity, and community cohesion. The study supports the application of STEAM in resource-scarce environments, noting its use to reduce the educational gap and build digital and analytical skills among rural school children. Further research in other regions with similar characteristics is recommended to expand the scope of these results.